Overview of Oxygen Saturation in COVID-19 Patients Before Dispatching From UKRIDA Hospital in 2021 - Citra Rencana Perangin-angin; Eva Oktavia; Chelna Feliarossa de Fretes (Jurnal MedScientiae, 2022)
Coronavirus disease 2019 (COVID-19) is a disease that attacks the respiratory system with risk factors in the form of age, gender, and comorbid diseases. In addition, COVID-19 can affect oxygen saturation levels. Oxygen saturation is an indicator of oxygenation status by looking at the percentage of oxygen content in the arteries that binds to hemoglobin. The normal value for oxygen saturation is 95-100%. Objective to knowing the description of oxygen saturation of research respondents before treatment and before being discharged from UKRIDA Hospital which is influenced by age, gender and comorbid diseases. This study used a consecutive sampling method with a cross sectional design. There were 96 subjects who met the inclusion and exclusion criteria. Data collection was carried out using medical record data for the period January 1, 2021 to July 31, 2021. The results of data analysis using Chi-square with the results obtained that age and comorbid diseases have a relationship with changes in oxygen saturation levels (p-value <0.05). Meanwhile, gender had no relationship to changes oxygen saturation levels . There is a relationship between age and comorbid disease with changes in oxygen saturation levels before being discharged from UKRIDA Hospital with an average oxygen saturation of 97%.